Efficient Protein Transduction Method Using Cationic Peptides and Lipids. (9th October 2011) - Yamaguchi, Kei; Inoue, Mari; Goshima, Naoki
Abstract : Cationic peptides termed protein transduction domains (PTDs) have been shown to cross biological membranes efficiently. However, proteins transduced by PTDs become entrapped within the endosomal vesicles and are not delivered into organelles. We have developed a novel protein delivery system to enhance the proton sponge effect, which results in rupture of the endosomes, by using a mixture of Wr-T transporter peptide and a commercially available cationic lipid reagent. This peptide and cationic lipid reagent mixture efficiently delivers a variety of cargo proteins into living cells by releasing them from the endosomes.